The Potential Contributions of Lethal and Edema Toxins to the Pathogenesis of Anthrax Associated Shock - Peter Q. Eichacker; Daniel A. Sweeney; Yan Li; Amisha Barochia; Xizhong Cui; Caitlin W. Hicks (Toxins, 2011)
Outbreaks of Bacillus anthracis in the US and Europe over the past 10 years have emphasized the health threat this lethal bacteria poses even for developed parts of the world. In contrast to cutaneous anthrax, inhalational disease in the US during the 2001 outbreaks and the newly identified injectional drug use form of disease in the UK and Germany have been associated with relatively high mortality rates. One notable aspect of these cases has been the difficulty in supporting patients once shock has developed. Anthrax bacilli produce several different components which likely contribute to this shock. Growing evidence indicates that both major anthrax toxins may produce substantial cardiovascular dysfunction. Lethal toxin (LT) can alter peripheral vascular function; it also has direct myocardial depressant effects. Edema toxin (ET) may have even more pronounced peripheral vascular effects than LT, including the ability to interfere with the actions of conventional vasopressors. Additionally, ET also appears capable of interfering with renal sodium and water retention. Importantly, the two toxins exert their actions via quite different mechanisms and therefore have the potential to worsen shock and outcome in an additive fashion. Finally, both toxins have the ability to inhibit host defense and microbial clearance, possibly contributing to the very high bacterial loads noted in patients dying with anthrax. This last point is clinically relevant since emerging data has begun to implicate other bacterial components such as anthrax cell wall in the shock and organ injury observed with infection. Taken together, accumulating evidence regarding the potential contribution of LT and ET to anthrax-associated shock supports efforts to develop adjunctive therapies that target both toxins in patients with progressive shock.